Pendampingan dan Peningkatan Kapasitas Daiyah Fatayat dalam Penguatan Dakwah - Khiyaroh, Intihaul (PARTISIPATORY, 2025)
This community service aims to provide assistance and increase the capacity of Fatayat preachers in Paciran District as an effort to strengthen women's da'wah in an adaptive and contextual manner. Through training and coaching, this program focuses on increasing missionary competence, mastering effective communication methods, and utilizing digital technology in conveying religious messages. It is hoped that this assistance can strengthen the role of Daiyah Fatayat in empowering women and the wider community, as well as responding to the challenges of social and cultural change in the digital era. The results of the activities showed an increase in self-confidence, da'wah abilities, and active involvement of da'iyah in various religious and social activities in Paciran. This program makes a significant contribution in strengthening an inclusive and progressive women's da'wah network at the local level. This community service research aims to provide assistance and increase the capacity of Fatayat preachers in the context of strengthening women's da'wah in Paciran District. The method used is a participatory approach with training, coaching and direct assistance to Fatayat preachers to improve their da'wah competence, effective communication skills and the use of digital technology in da'wah. The findings show a significant increase in da'wah abilities, self-confidence, and active involvement of da'iyah in religious and social activities at the local level. The novelty of this program lies in the integration of andragogy-based training methods and the use of digital media adapted to the local context of Paciran, which has not been widely applied in strengthening women's da'wah in the area. The contribution resulting from this service is in the form of strengthening an inclusive and progressive women's da'wah network, as well as increasing the capacity of the Fatayat daiyah as an agent of social and religious change in the Paciran District community.